Morphological Assessment of Maxillary Sinus Septa Variations with Cone-Beam Computed Tomography in a Turkish Population - Kocak, Nazan; Alpoz, Esin; Boyacıoglu, Hayal (European Journal of Dentistry, 2019)
Objective The purpose of this study was to measure and classify sinus septa variables (prevalence, numbers, heights, locations, orientations, and morphology) and to determine the effects of age, gender, and dental status on the presence of septa and also to evaluate the effects of septa on pathological mucosal thickening.Materials and Methods A total of 2,000 patients were analyzed through conebeam computed tomography (CBCT). The total of 500 maxillary sinuses were included in this study. The number of maxillary sinus septa was determined on axial sections of CBCT images. Their locations, orientations, and morphologies were determined on both the axial and sagittal sections, and their heights were determined only on the sagittal sections. The influence of age, gender, dental status, and pathological mucosal thickening on the presence of septa was statistically analyzed. Mann–Whitney U-test and descriptive statistics were used for statistical analysis.Results The average height of the determined 287 septa was measured as 7.36 mm. The highest rates of septa location, morphology, and orientation were found, respectively, in the middle region septa (57.49%), completed septa (75.95%), and transverse septa (93.37%). The effect of dental status, age, and gender on the presence of septa was not statistically significant (p > 0.05).Conclusion These high rates of findings support the importance of CBCT in the diagnosis of the variations of the maxillary sinus septa. Therefore, it is important to evaluate CBCT images of the relevant region to increase the success of surgical interventions in the maxillary posterior region and to eliminate possible complications.
Keywords: cone-beam computed tomography; maxillary sinus; septa; sinus floor augmentation